Institutions and firm growth in a transitional and post-conflict economy of Kosovo. Issue 2 (15th October 2018) - Krasniqi, Besnik; Branch, David
Abstract : Purpose: The quality of institutions matters for firm growth. Yet, there is a research gap in controlling for moderating effect of size on institutions and firm growth in transitional context and especially in post-conflict economies. Building on institutional theory, this research aims to explore the influence of different types of institutional variables (taxes, corruption, administrative, finance and other barriers) on the growth of firms in Kosovo, while controlling for the firm size moderating effect. Design/methodology/approach: The research uses linear regression analysis based on a survey with 451 owner-managers of growing small firms in the post-conflict economy of Kosovo. Findings: Corruption and administrative burden are crucial factors that influence firm growth. Corruption is found to have a negative effect, and when moderated by the size of the firm, it becomes positive, suggesting that larger firms make use of informal institutions and create links with public officials to manage institutional deficiencies. This size interaction with administrative barrier variables becomes positive. Other control variables (export status, separation of ownership and control, membership in business association) suggest that managerial-level variables have a positive impact on firm growth. The human capital variable specifically indicates that companies compensate for a deficiency in formal education by providing additional training for employees and their managers. Research limitations/implications: Future research based on qualitative research can contribute to a greater understanding of how larger firms use resources to overcome barriers, and to align their business strategies in the weak post-conflict environments. Originality/value: This research extends current understanding of how institutional variables interact with firm size and impact firm growth. It also provides implications for policymakers and entrepreneurs/managers for improving the growth of SMEs, and for aligning firms with the institutional environment in post-conflict countries.